Distinct bacterial community structure and composition along different cowpea producing ecoregions in Northeastern Brazil - Luciana de Sousa Lopes (Nature Portfolio, 2021)
Abstract Soil microbial communities represent the largest biodiversity on Earth, holding an important role in promoting plant growth and productivity. However, the knowledge about how soil factors modulate the bacteria community structure and distribution in tropical regions remain poorly understood, mainly in different cowpea producing ecoregions belonging to Northeastern Brazil. This study addressed the bacterial community along three different ecoregions (Mata, Sertão, and Agreste) through the16S rRNA gene sequencing. The results showed that soil factors, such as Al3+, sand, Na+, cation exchange excel, and total organic C, influenced the bacterial community and could be a predictor of the distinct performance of cowpea production. Also, the bacterial community changed between different ecoregions, and some keystone groups related to plant-growth promotion, such as Bradyrhizobium, Bacillales, Rhizobiales, and Solibacillus, were correlated to cowpea yield, so revealing that the soil microbiome has a primordial role in plant productivity. Here, we provide evidence that bacterial groups related to nutrient cycling can help us to increase cowpea efficiency and we suggest that a better microbiome knowledge can contribute to improving the agricultural performance.